Virtual victims? Insecurity, audiences and social networking services in Argentina - Galar, Santiago; Focás, Brenda (InMediaciones de la Comunicación, 2018)
Recently, the Internet has become a platform for online interaction processes that has expanded the possibility of participation to non-expert users. In this context, insecurity, as an issue, has become in a common theme for its dissemination and debate through virtual spaces. In this article we propose to investigate the practices in social networking services exercised by publics that are shaped around insecurity in Argentina during the last decade, paying particular attention to the practices of those relatives of victims of crime. With this objective we investigate different experiences: firstly, we analyze practices and emerging contents of three spaces in social networking services linked to cases of insecurity. Secondly, we conducted in-depth interviews with administrators from different pages (or fanpages) and Facebook open groups linked to the experience of victimization and insecurity. Finally, we participate in collective street actions linked to the organization and demand of these virtual groups, particularly a march for security. The work focuses on the dynamics of the processes that converge in these experiences and the practices of the actors that give them entity. We perform a qualitative analysis.